Contrasting Roles of Islet Resident Immunoregulatory Macrophages and Dendritic Cells in Experimental Autoimmune Type 1 Diabetes. - Thomas B Thornley; Krishna A Agarwal; Periklis Kyriazis; Lingzhi Ma; Vaja Chipashvili; Jonathan E Aker; Sarantis Korniotis; Eva Csizmadia; Terry B Strom; Maria Koulmanda (PLoS ONE)
The innate immune system critically shapes diabetogenic adaptive immunity during type 1 diabetes (T1D) pathogenesis. While the role of tissue-infiltrating monocyte-derived macrophages in T1D is well established, the role of their tissue-resident counterparts remains undefined. We now demonstrate that islet resident macrophages (IRMs) from non-autoimmune mice have an immunoregulatory phenotype and powerfully induce FoxP3+ Tregs in vitro. The immunoregulatory phenotype and function of IRMs is compromised by TLR4 activation in vitro. Moreover, as T1D approaches in NOD mice, the immunoregulatory phenotype of IRMs is diminished as is their relative abundance compared to immunostimulatory DCs. Our findings suggest that maintenance of IRM abundance and their immunoregulatory phenotype may constitute a novel therapeutic strategy to prevent and/or cure T1D.